2021
DOI: 10.31590/ejosat.994387
|View full text |Cite
|
Sign up to set email alerts
|

Örgütsel Adalet Algısı ve Mobbingin İş Tatmini ve İşten Ayrılma Niyetine Etkisinin İncelenmesi

Abstract: ÖzGünümüz rekabet koşullarında bilginin kurumsal belleğe aktarılması firmalara rekabet avantajı sağlayan önemli konulardan biridir. Çalışanların edindikleri bilgileri şirketlere kazandırabilmeleri için şirketin çalışan devir hızının düşük olması gerekmektedir. Bu nedenle deneyimli çalışanları kaybetmek kurumsal olmak isteyen firmalar için önemli bir kayıptır. Bu çalışmada, çalışanların örgütsel adalet algılarının ve maruz kaldıkları mobbingin, şirketten ayrılma isteklerine, iş tatminlerine ve işe bağlılıkların… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In addition, it has been found that human resources management practices are effective in employees' intention to quit work, and that human resources practices positively affect employees' emotional states, thus reducing that intention (Hossain et.al., 2017;Tuysuz & Bozkurt, 2021). In a limited number of studies similar to the model of our research, it is stated that human resources practices can reduce the intention to quit work, and that negative behaviors such as mobbing can be prevented with right strategies (Gunduz & Bekmezci, 2012;Ozturk, 2021;Kahriman, 2021;Atalay & Dogan, 2020;Grass, 2022). On the other hand, according to our findings higher levels of mobbing increase intention to quit the work directly but decrease human resources practices, which, in turn, increase intention to quit the work.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, it has been found that human resources management practices are effective in employees' intention to quit work, and that human resources practices positively affect employees' emotional states, thus reducing that intention (Hossain et.al., 2017;Tuysuz & Bozkurt, 2021). In a limited number of studies similar to the model of our research, it is stated that human resources practices can reduce the intention to quit work, and that negative behaviors such as mobbing can be prevented with right strategies (Gunduz & Bekmezci, 2012;Ozturk, 2021;Kahriman, 2021;Atalay & Dogan, 2020;Grass, 2022). On the other hand, according to our findings higher levels of mobbing increase intention to quit the work directly but decrease human resources practices, which, in turn, increase intention to quit the work.…”
Section: Discussionmentioning
confidence: 72%
“…Tilki et al's (2021) had conducted a research with disabled employees and found that factors like organizational cynicism and job satisfaction are also effective on the intention to quit work, along with mobbing. According to Kahriman et al (2021), while the employees' perception of mobbing behavior and their intention to quit work have a positive relationship, this situation also affects the job satisfaction of the employees negatively. Focusing on mobbing behavior, these studies take intention to quit work and job dissatisfaction as individual outputs; inefficiency, poor performance, employee turnover, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Bu bağlamda bireylerin yaşam doyumları, iş tatminleri (doyumları) ve iş dışı yaşam tatminlerine bağlıdır Özdevicioğlu & Çakmak Doruk, 2009). Farklılıkların yönetimi uygulamalarının iş tatminini yüksek düzeyde etkilediği bulunmuştur (Ordu, 2016;Saraç vd., 2020), yine örgütsel adalet algısının da iş tatminini olumlu etkilediği ortaya çıkmıştır (Kahrıman, Avcı & Aladağ, 2021;Pehlivan Kurnaz & Oruç, 2019). İşten ayrılma niyeti ile yaşam doyumu arasında orta düzeyde anlamlı bir ilişki olduğu saptanmıştır (Çelik & Toker, 2016).…”
Section: Introductionunclassified